2, 4‐Dinitrophenol: 'diet' drug death following major trauma. Issue 1 (18th May 2021) - Freeman, N.; Moir, D.; Lowis, E.; Tam, E.
Summary: There has been a resurgence in the illicit use of 2, 4‐dinitrophenol by people wishing to achieve rapid weight loss. Despite its availability, the drug is banned for human consumption as it is toxic and can have fatal consequences. We present the case of a 23‐year‐old man who regularly consumed 2, 4‐dinitrophenol to generate fat loss without apparent ill effect. He was involved in a high‐speed road traffic collision and sustained limb‐threatening injuries. The combination of emergency surgery, trauma and 2, 4‐dinitrophenol consumption culminated in deterioration under anaesthesia, with subsequent death from multiorgan failure in the intensive care unit 48 h later. Previous cases have reported death from 2, 4‐dinitrophenol toxicity alone. We believe this is the first reported case of 2, 4‐dinitrophenol toxicity triggered by the additional physiological stress of polytrauma and emergency surgery.